Екологічна оцінка вод річок басейну р. Сян у межах України - Кость, М.; Паньків, Р.; Сахнюк, І.; Козак, Р.; Майкут, О.; Березовський, І. (Геологія і геохімія горючих копалин, 2010)
Досліджено особливості розподілу Fe, Sr, Mn, Ba, Ti, Zn, Li, Cr, Cu, V, Mo, Pb, Ni, Co та Cd у річках Шкло, Завадівка, Гребелька, Гноєнець, Ретичин, Вишня (Львівська обл.). Проведено екологічну оцінку якості вод за ступенем їхньої чистоти (забрудненості). Води поганої якості – брудні – має р. Ретичин (Mn), посередньої якості – помірно забруднені – річки Шкло (Fe, Mn), Гноєнець (Mn), Вишня (Fe, Mn), Завадівка (Mn). Задовільну якість мають слабко забруднені води р. Гребелька (Mn, Fe). Основними джерелами забруднення вод мікроелементами є добрива, підземні води, відходи флотації сірчаних руд, комунально-побутові стоки. This paper presents the results of studying peculiarity of the distribution of Fe, Sr, Mn, Ba, Ti, Zn, Li, Cr, Cu, V, Mo, Pb, Ni, Co and Cd in the Shklo, Zavadivka, Hrebelka, Vyshnya rivers in the Lviv Region. The water quality was estimated ecologically based on the level of water purity (pollution). The total distribution of microelements in waters of the rivers looks as follows: Fe > Sr > Mn > Ba > Ti > Zn > Li > Cr > Cu > V > Mo > (Pb, Ni, Co, Cd). The concentration of the elements ranges within the following limits (mg/dcm 3 ): Fe 0.03–4.30; Sr 0.28–2.73; Mn 0.010–2.246; Ba 0.03–0.20; Ti <0.002– 0.166; Zn 0.002–0.083; Li <0.001–0.054; Cr <0.0007–0.0096; Cu <0.0020–0.0068; V <0.0020–0.0103; Mo <0.0030–0.0067; Pb <0.01; Ni <0.005; Co <0.002; Cd <0.001. In waters of the rivers, Cd, Co, Pb and Ni were found in lesser quantities than those indicated in accepted sanitary-hygienic standards regardless of seasons. Concentrations of Cu and Sr in waters of the rivers become somewhat increased in the autumn, but Mn, Zn and Fe – become decreased. Concentrations of metals become decreased or do not change running with the stream of the River Zavadivka, but become increased running with the stream of the River Shklo, especially sharply after its running – out from the Lake Yavoriv. The highest concentrations of Sr, Li, Fe, Zn and Mn were found in waters of the medium stream of the River Shklo. Waters of bad quality – polluted – were observed in the River Retychyn (Mn). The average quality – moderately polluted – was observed in Shklo (Mn, Fe), Hnoyenets (Mn), Vyshnya (Fe, Mn) and Zavadivka (Mn) rivers. Satisfactory quality was observed in waters of the River Hrebelka (Mn, Fe). The main sources of the pollution of waters with microelements are: fertilizers, ground waters, waste of flotation of sulphur ores, domestic sewage. Obtained data as to the state of surface waters of the Lviv Region point out rather difficult sanitary-hygienic conditions that, in its turn, causes the necessity to take all due measures to prevent pollution of the environment with the purpose of approximating of the quality of these waters to ecological standards for the purity of surface waters on land.